2014
DOI: 10.1108/jmp-02-2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

Early career attitudes and satisfaction during recession

Abstract: Early career attitudes and satisfaction during recession AbstractPurpose -To examine the role of protean and boundaryless career attitudes in early career employees during a time of economic recession in Ireland, specifically regarding their relationship to work characteristics, job satisfaction and career satisfaction. Findings -Skill variety was related to higher job satisfaction for those with a strong organizational mobility preference, and skill specialization was related to lower job satisfaction for tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 65 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…Moreover, self-directed workers are more likely to be satisfied with both their jobs and their careers (Briscoe, Henagan, Burton, & Murphy, 2012;O'Shea, Monaghan, & Ritchie, 2014). In contrast, those who follow their own values when making career choices (i.e., values-driven) are less likely to exhibit these outcomes (Briscoe & Finkelstein, 2009;Ç akmak-Otluoglu, 2012).…”
Section: Work and Career Outcomesmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, self-directed workers are more likely to be satisfied with both their jobs and their careers (Briscoe, Henagan, Burton, & Murphy, 2012;O'Shea, Monaghan, & Ritchie, 2014). In contrast, those who follow their own values when making career choices (i.e., values-driven) are less likely to exhibit these outcomes (Briscoe & Finkelstein, 2009;Ç akmak-Otluoglu, 2012).…”
Section: Work and Career Outcomesmentioning
confidence: 95%
“…Research suggests that workers who hold self-directed (protean) career attitudes often express feelings of attachment to their organizations (i.e., organizational commitment), perceive themselves to be capable of maintaining or acquiring new employment, and may engage in more job search activities (Çakmak-Otluoğlu, 2012; De Vos & Soens, 2008; Waters, Briscoe, Hall, & Wang, 2014). Moreover, self-directed workers are more likely to be satisfied with both their jobs and their careers (Briscoe, Henagan, Burton, & Murphy, 2012; O’Shea, Monaghan, & Ritchie, 2014). In contrast, those who follow their own values when making career choices (i.e., values-driven) are less likely to exhibit these outcomes (Briscoe & Finkelstein, 2009; Çakmak-Otluoğlu, 2012).…”
Section: Study 2: Scale Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been observed that older people are much more likely to be involved in FPR (Hershey et al, 2007). In Spain, history-related influences could be exemplified by the pensions system reform conducted in 2011 and 2013, which increased the population’s awareness about the sustainability of future pensions (Budowski, Schief, & Sieber, 2016), or by differences in formal education among cohorts (O’Shea, Monaghan, & Ritchie, 2014), which provide them with different skills in order to handle financial information. Finally, nonnormative life events, such as major health problems (Assari & Lankarani, 2016), could interfere with FPR, and empirical support has recently been found for this assertion (Han, Boyle, James, Yu, & Bennett, 2015).…”
Section: Retirement Planning and Agementioning
confidence: 99%
“…Ireland was one country severely impacted by the global financial crisis which began in September 2007 (Mercille & Murphy, 2017;O'Shea, Monaghan, & Ritchie, 2014;Russell & McGinnity, 2014). It provides an appropriate environment to examine how psychological workplace interventions operate in omnibus contexts that impose high job demands and low job resources.…”
mentioning
confidence: 99%